Pidhotovka sportsmeniv vysokoyi kvalifikaciyi v umovax profesionalizaciyi sportu (na prykladi lehkoyi atletyky) - Kozlova, O. (Teorija i metodika fizichnogo vihovannja, 2013)
Objective. Improving the training of athletes of high qualification in conditions of professionalization of track and field sports is based on the identification of trends in modern system of competitions and competitive activities. Methods. Analysis and review of scientific and methodological literature, information from Internet, calendars, reports, and ratings of competitions; methods of mathematical statistics. Results. The modern system of competition in track and field is in continuous development and defined by the expansion of sports calendars, emergence of new formats and categories of events aimed to generate revenue from their implementation. Despite the expansion of sports calendar, professionalization in track and field sport leads to decrease in the number of competitions in sport elite. Conclusions. Improving the efficiency of competitive activity of athletes of high qualification assumes reduction in the number of competitions per year and their rational distribution to reach a peak of readiness in major competitions as well as demonstration of high sport performance in the optimal number of significant competition attended by personal invitation.